2021
DOI: 10.1111/trf.16530
|View full text |Cite
|
Sign up to set email alerts
|

Cold‐stored platelets have better preserved contractile function in comparison with room temperature‐stored platelets over 21 days

Abstract: Although it is well established that transfusion of platelets in cases of severe bleeding reduces mortality, the availability of platelets is hampered by harsh restrictions on shelf life due to elevated risks of microbial contamination and functional losses with room temperature‐stored platelets (RTP) kept at 22°C. In contrast, many recent studies have shown that 4°C cold‐stored platelets (CSP) are able to overcome these shortcomings leading to the recent Food and Drug Administration licensure for 14‐day store… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 51 publications
1
21
0
Order By: Relevance
“…We and others have provided evidence for the in vitro functionality of CS‐PLT stored out to 21 days. Others have also demonstrated that CS‐PLT stored in PAS out to 21 days have been shown to be non‐inferior to RT‐PLT stored for 5 days as assessed by in vitro assessments 42,43 . These data are supportive of increasing the shelf life of CS‐PLT out to 21 days, however, we do not currently have safety or efficacy data regarding day 21 CS‐PLT transfusion in humans.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…We and others have provided evidence for the in vitro functionality of CS‐PLT stored out to 21 days. Others have also demonstrated that CS‐PLT stored in PAS out to 21 days have been shown to be non‐inferior to RT‐PLT stored for 5 days as assessed by in vitro assessments 42,43 . These data are supportive of increasing the shelf life of CS‐PLT out to 21 days, however, we do not currently have safety or efficacy data regarding day 21 CS‐PLT transfusion in humans.…”
Section: Discussionmentioning
confidence: 66%
“…Others have also demonstrated that CS-PLT stored in PAS out to 21 days have been shown to be non-inferior to RT-PLT stored for 5 days as assessed by in vitro assessments. 42,43 These data are supportive of increasing the shelf life of CS-PLT out to 21 days, however, we do not currently have safety or efficacy data regarding day 21 CS-PLT transfusion in humans. The CHIPS trial (NCT04834414), a multicenter randomized controlled trial comparing RT-PLT to CSP-PLT in actively bleeding cardiac surgery patients, includes an adaptive design that will allow for the extension of CS-PLT storage from 7 days out to 21 days if they remain non-inferior to the RT-PLT group.…”
Section: Discussionmentioning
confidence: 92%
“…The superior fiber crosslinking in CPs could be mediated by factor XIII through binding on the activated glycoprotein IIb/IIIa on the CPs surfaces [20]. In addition, clot histology showed that CPs had higher porosity and more well-defined structure in their clots similar to fresh platelets [21]. On the other hand, RPs formed clots with altered structure and decreased porosity.…”
Section: Cps In Vitro Characterization: An Update and A Debatementioning
confidence: 99%
“…compare the in-vivo properties of RT and cold-stored WB for haemostasis during surgery. Second, cold storage induces many changes in platelets not corresponding with aging or storage lesions of platelets stored at RT [28][29][30]. These changes can be influenced by several factors such as the levels of surface-receptor modifications, platelet-activation markers, and thrombotic microparticles, that were not measured herein.…”
Section: Plos Onementioning
confidence: 94%